2018
DOI: 10.1016/j.artd.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Femoral artery injury during total hip arthroplasty

Abstract: There are an increasing number of vascular complications after hip replacement, some of which can be life-threatening. However, there are few reports of lower limb ischemic symptoms after undergoing an otherwise uncomplicated classic total hip replacement. We report a patient with low weight who developed postoperative limb ischemia resulting from blood clots caused by insertion of a Hohmann retractor close to small anterior acetabular osteophytes. Ultrasonography and angiography revealed her symptoms to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…puncture injuries or arterial lacerations), iii) false aneurysms, and iv) heat induced arterial thrombosis due to polymerization of bone cement. (4,(6)(7)(8) Clinical signs and symptoms of these injuries can arise within the immediate post-operative period, or in a delayed fashion as demonstrated by our case. The most common manifestations of vascular injuries include intraoperative haemorrhage, post-operative ischaemic symptoms from impaired flow or acute thrombosis, or delayed joint pain and soft tissue swelling from pseudoaneurysms.…”
Section: Discussionmentioning
confidence: 56%
“…puncture injuries or arterial lacerations), iii) false aneurysms, and iv) heat induced arterial thrombosis due to polymerization of bone cement. (4,(6)(7)(8) Clinical signs and symptoms of these injuries can arise within the immediate post-operative period, or in a delayed fashion as demonstrated by our case. The most common manifestations of vascular injuries include intraoperative haemorrhage, post-operative ischaemic symptoms from impaired flow or acute thrombosis, or delayed joint pain and soft tissue swelling from pseudoaneurysms.…”
Section: Discussionmentioning
confidence: 56%
“…Intrapelvic acetabular screw penetration during THA is known to be potentially hazardous with serious and often immediate associated complications [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. While mispositioned acetabular screws typically have acute or subacute implications, intrapelvic screw penetration may also be problematic remote from the index procedure [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The placement of transacetabular screws is recognized to have associated risk, and close attention must be paid to the extrapelvic acetabular quadrant in which these are placed [ [6] , [7] , [8] , [9] ]. A multitude of complications have been reported with aberrant screw placement including arterial laceration, [ 10 ] arterial pseudoaneurysm formation, [ [11] , [12] , [13] , [14] ] bladder injury, [ 15 ] and nerve irritation, [ 16 ] among others [ 17 ]. Arterial injury, in particular, during THA has been reported to occur in 0.08%-0.3% of cases [ [18] , [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] It occurs frequently in female patients and on the left side in arthroplasty, which reflects the closer proximity of the vessels to the hip joint in these 2 categories. [ 5 ] However, Shuai et al [ 6 ] described that other factors such as the type of surgery (infection or revision) might be more important for the vascular injury. Abularrage et al [ 7 ] reported an increase in the incidence of 0.04% in primary THA to 0.19% in revision surgery.…”
Section: Discussionmentioning
confidence: 99%